The Procedural Difference between the Main Third-Party Intervention and Derivative in the Preliminary Stage and Reconsideration - Majid Aziziyani (پژوهشهای حقوقی)
Judicial supervision is considered as integral part of the process. In two legal systems of Iran and France, these two Fights are acceptable in the appeal stage. A comparative study of the two entities in the two legal systems shows that in most rules they are similar and there are slight differences between them. Third-party involvement in the appeal stage is one of the exceptions to the principle of prohibition of interference by persons other than the parties to the case The deadline for a third-party litigation in Iran is until the end of the first hearing, while in France until the end of the investigation. The condition of acceptance of a lawsuit in France is the transformation of the lawsuit. The transformation of litigation occurs when new facts of truth or a are discovered. The jurisdiction of a judge to obtain a third party under certain conditions in French law is another difference with Iran, while in Iran this is not possible. Some of the rules of third party intervention in the appeal stage are not mentioned in the law and must be determined by law. Third-party Claims in French law are admissible upon termination.